2019
DOI: 10.1002/acm2.12710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CT reconstruction algorithm on auto‐segmentation performance

Abstract: Model‐based iterative reconstruction (MBIR) reduces CT imaging dose while maintaining image quality. However, MBIR reduces noise while preserving edges which may impact intensity‐based tasks such as auto‐segmentation. This work evaluates the sensitivity of an auto‐contouring prostate atlas across multiple MBIR reconstruction protocols and benchmarks the results against filtered back projection (FBP). Images were created from raw projection data for 11 prostate cancer cases using FBP and nine different MBIR rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The FBP algorithm has the characteristics of simple operation and short running time when processing CT images, but it has the problem of high radiation dose and needs to be further optimized [ 19 ]. In order to reduce the harm of X-rays to the human body, the CT image is reconstructed, the ROI projection data is used to increase or decrease the projection data of the region of interest (ROI), and the constructor is used to reconstruct the overall or partial image [ 20 ]. For the convolutional backprojection calculation of image reconstruction, the ROI area can be selected, and it is not necessary to scan the whole to obtain all the projection data [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FBP algorithm has the characteristics of simple operation and short running time when processing CT images, but it has the problem of high radiation dose and needs to be further optimized [ 19 ]. In order to reduce the harm of X-rays to the human body, the CT image is reconstructed, the ROI projection data is used to increase or decrease the projection data of the region of interest (ROI), and the constructor is used to reconstruct the overall or partial image [ 20 ]. For the convolutional backprojection calculation of image reconstruction, the ROI area can be selected, and it is not necessary to scan the whole to obtain all the projection data [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…e noise level and the overall image were improved. Miller et al [18] used the CT reconstruction algorithm to analyze the automatic segmentation performance of the image, and the iterative reconstruction algorithm had greatly improved the automatic segmentation performance. e results of this study also showed that the image quality, blood vessel sharpness, average image score, SNR, and radiation dose of the algorithm were all increased, while the value of noise was reduced, suggesting that the algorithm showed obvious advantages in image processing.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial resolution and signal-to-noise ratio optimization as well as artifact limitations are prerequisites for constructing useful postprocessing result [15][16][17]. There is no doubt that recent technological developments have strengthened postprocessing possibilities and expanded its applications.…”
Section: Prerequisitesmentioning
confidence: 99%